Effects of Juvenile Idiopathic Arthritis on Kinematics and Kinetics of the Lower Extremities Call for Consequences in Physical Activities Recommendations - M. Hartmann; F. Kreuzpointner; R. Haefner; H. Michels; A. Schwirtz; J. P. Haas (International Journal of Pediatrics)
Juvenile idiopathic arthritis (JIA) patients (n=36) with symmetrical polyarticular joint involvement of the lower extremities and healthy controls (n=20) were compared concerning differences in kinematic, kinetic, and spatio-temporal parameters with 3D gait analysis. The aims of this study were to quantify the differences in gait between JIA patients and healthy controls and to provide data for more detailed sport activities recommendations. JIA-patients showed reduced walking speed and step length, strongly anterior tilted pelvis, reduced maximum hip extension, reduced knee extension during single support phase and reduced plantar flexion in push off. Additionally the roll-off procedure of the foot was slightly decelerated. The reduced push off motion in the ankle was confirmed by lower peaks in ankle moment and power. The gait of JIA-patients can be explained as a crouch-like gait with hyperflexion in hip and knee joints and less plantar flexion in the ankle. A preventive mobility workout would be recommendable to reduce these restrictions in the future. Advisable are sports with emphasis on extension in hip, knee, and ankle plantar flexion.